Biology Teacher Emotional Intelligence Analysis towards Class X IPA Students in State High School in the District of Pangkatan - Ayu Sari Purba; Hasmi Syahputra Harahap (Budapest International Research and Critics University, 2022)
Emotional intelligence is the ability of a person to know one's feelings for oneself or others, and encourage oneself to be able to control one's emotions well and behave in a scientific manner that is able to accept the opinions of others. X IPA at state high schools in all sub-districts. This type of research uses qualitative with the method used is descriptive. The population used was 6 public high school teachers in Pangakatan District, while the total sampling sample consisted of 6 State Senior High School teachers in Pangkatan District, Data collection techniques were carried out by giving direct interviews and questionnaire responses to teachers regarding the emotional intelligence of biology teachers to students by direct distribution instruments in the form of questionnaires and questionnaires The data analysis technique uses descriptive analysis before carrying out descriptive analysis. The results of the study are that teachers who recognize self-emotions get a score of 65.92% then teachers who can manage their own emotions get 56.85% results, then teachers who can motivate themselves themselves get 62.42% results, and teachers who can recognize other people's emotions get 44.68% results and teachers who can build relationships with other people get 57.81% results. There are still teachers who have not been able to control the emotional intelligence of Class X IPA students at State Senior High Schools throughout the Pangkatan District.